An Assessment of Satisfaction with Ambulatory Child Psychiatry Consultation Services to Primary Care Providers by Parents of Children with Emotional and Behavioral Needs: The Massachusetts Child Psychiatry Access Project University of Massachusetts Parent Satisfaction Study - Dvir, Yael; Wenz-Gross, Melodie; Jeffers-Terry, Mary; Metz, W P. (Frontiers in Psychiatry, 2012)
This study evaluated parents’ experience with University of Massachusetts (UMass) Child Psychiatry Access Project (MCPAP), a consultation service to primary care providers (PCP), aimed at improving access to child psychiatry. Parent Satisfaction Questionnaire (PSQ) was sent to families referred to UMass MCPAP by their PCP, asking about their concerns leading to the referral, the satisfaction from the service provided, adequacy of the follow up plan, and outcome. Seventy nine percent of parents agreed or strongly agreed that the services provided were offered in a timely manner. Fifty percent agreed or strongly agreed that their child’s situation improved following their contact with the services. Sixty nine percent agreed or strongly agreed that the service met their family’s need. The results suggest moderate to high parental satisfaction with MCPAP model, but highlight ongoing challenges in making successful referrals for children’s mental health services in the community, following MCPAP recommendations.